Cultural Meaning on Traditional Equipment of The Healing Ritual Tradition of Anak DalamTribes in The Batin Sembilan Community, Muaro Jambi District: The Efforts to Preserve Local Wisdom - Helty; Izar, Julisah; Wilyanti, Liza Septa; Maisaroh, Siti (Mudra Jurnal Seni Budaya, 2024)
This research aimed to inventory the cultural meaning of traditional ritual equipment and document the equipment used during the tradition of healing requests of Anak Dalam Tribes Batin Sembilan Muaro Jambi Regency as a form of effort to maintain local wisdom. Meanwhile, the research method in this research used a qualitative descriptive method with an ethnographic approach. Data collection techniques in this research used interviews and documentation, while data analysis techniques used data reduction techniques, data presentation and conclusions. The results of the research show various descriptions and documentation of the cultural meaning of the equipment used during the tradition of healing requests of Anak Dalam tribes in Batin Sembilan Muaro Jambi Regency as a form of effort to maintain local wisdom. The names of the tools used in this tradition include: Balai, sesaji, Balai Pengadap, Ancak Kembang, Dupo dan orang-orangan and these are large tools that are used in general while other tools used include: Bertih, Cace, Balai di atas balai, cengkraman, redap, bedak kramasan, nampan sirih tambang balai, kain andam, gambar koneng dan cawan.